Teaching nonviolent communication to increase empathy between people and toward wildlife to promote human–wildlife coexistence. Issue 1 (6th January 2022) - Kansky, Ruth; Maassarani, Tarek
Abstract: Promoting human–wildlife coexistence in complex systems where both relationships between people and toward wildlife need to be managed is challenging. We applied nonviolent communication (NVC) training as part of a participatory dialogue program to increase empathic concern toward wildlife and between people to promote human–wildlife coexistence. NVC was developed in the 1960s by Marshal Rosenberg, a clinical psychologist who sought to incorporate empathy and compassion into everyday language. Using weekly reflexive feedback from participants, we collected 36 examples of attitude change and 71 examples of behavior change that demonstrated increased empathic concern for both people and wildlife. Therefore, NVC training has potential to be an effective tool to increase empathy and promote tolerance and human–wildlife coexistence. This is the first attempt to use NVC in the biodiversity sector, and we believe these results show promise for its wider application as a tool for participatory dialogues to improve collaboration, understanding and resolve conflicts.